2017
DOI: 10.1007/s10597-017-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Families in Assertive Community Treatment (ACT) Teams in Norway: A Cross-Sectional Study on Relatives’ Experiences of Involvement and Alienation

Abstract: International research shows that relatives of people with mental illness are rarely involved by mental health services. Assertive Community Treatment (ACT) has been recently implemented in Norway. The experience of relatives of ACT users is largely unknown. The aim of this study was to explore relatives' experience with ACT-teams in Norway. Data were collected using the family involvement and alienation questionnaire, consisting of experiences of approach, and alienation from the provision of professional car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Previous studies where the FIAQ was used indicate that a higher level of the experience of being approached positively is associated with a lower level of feelings of alienation and vice versa (Ewertzon et al., ; Weimand, Israel, & Ewertzon, ). This result is in accordance with the theoretical frameworks described above.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies where the FIAQ was used indicate that a higher level of the experience of being approached positively is associated with a lower level of feelings of alienation and vice versa (Ewertzon et al., ; Weimand, Israel, & Ewertzon, ). This result is in accordance with the theoretical frameworks described above.…”
Section: Introductionmentioning
confidence: 99%
“…The assessments in the FIAQ-R are subjective and the data consists of ordered categories. As in previous studies using the FIAQ or the FIAQ-R [10][11][12][17][18][19] data were analyzed using rank-based, non-parametric statistical methods. 20 The median level (Md) and quartiles (Q 1 ;Q 3 ) were used to describe the response profiles.…”
Section: Data Analysis Statistical Analysesmentioning
confidence: 99%
“…This concept has been studied among family members in the context of psychiatric care. [10][11][12] These studies showed that being approached positively by the health care professionals was associated with a lower level of feeling of alienation. To our knowledge, there has been no research concerning alienation among family members in the context of the care of older people.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Family members' views on the opportunities for meaningful activity in the SH context could therefore be important for identifying possible limitations in this aspect of housing support and generating ideas as to how to improve the support. The perceptions of family members can be used to form a positive alliance between the family members and the staff, which may in turn benefit the residents (Weimand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%